1984
DOI: 10.1288/00005537-198404000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Excisional biopsy in the selective management of T1glottic cancer: A three‐year follow‐up study

Abstract: Transoral excisional biopsy has been used in the evaluation and management of 103 T1 glottic cancers. A 3-year follow-up on these patients indicates that excisional biopsy unequivocally established the diagnosis and stage of the disease and that it is adequate treatment for micro and mini squamous cell cancers of the glottis in which the margins of excision are clear. Excisional biopsy with positive margins and larger T1 tumors establishes the absolute need for radiotherapy. Excisional biopsy is ideal for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
1
2

Year Published

1986
1986
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 11 publications
0
68
1
2
Order By: Relevance
“…Our results are similar to those of CO 2 treatment of recurrent glottic carcinoma reported in the literature. Blakeslee et al 14 reported a 40% success rate and think that extension of the tumor into the anterior commissure is a contraindication for laser surgery. Casiano et al 15 found a 5-year cure rate of 51% in previously irradiated patients, and the success rate was reduced (45% vs 65%) if the anterior commissure was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those of CO 2 treatment of recurrent glottic carcinoma reported in the literature. Blakeslee et al 14 reported a 40% success rate and think that extension of the tumor into the anterior commissure is a contraindication for laser surgery. Casiano et al 15 found a 5-year cure rate of 51% in previously irradiated patients, and the success rate was reduced (45% vs 65%) if the anterior commissure was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Orvidas et al 11 noted no cases these two modalities, 6,8,12 and other nonsurgical treatments 12,17 have also been employed, probably because the lesions were extensively overgrown, or because the patients had medical problems ruled out a radical operation, or because the patients did not wish to undergo operative treatments. We also noted specific treatment modalities for VC in the literature, such as photodynamic therapy, 17 administration of bleomycin (BLM), 16 cryosurgery, 18 laser surgery, 19,20 and the administration of recombinant alfainterferon. 12 These methods may be acceptable for some OVCs, but their "efficiency" has yet to be established because of the few patients treated by each method.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment option allows one-session therapy with an endoscopic approach, less morbidity, and fewer side effects, and cost-effectiveness as compared with the prolonged hospitalization for open surgery or a 5-to 6-week course of radiotherapy. Excellent success rates in the range of 89% to 96% have been reported by Blakeslee et al (1984), Ossoff et al (1985), Koufman (1986), Wetmore et al (1986, , and Thumfart (1993). It is important, however, not to overextend the indications of this extremely useful technology to larger tumors.…”
Section: Resultsmentioning
confidence: 78%